Implementing Islamic Values in Sharia Tourism Practices: A Case Study of the Sapuro Religious Tourism Destination in Pekalongan - Adinugraha, Hendri Hermawan; Surur, Achmad Tubagus; Al-Kasyaf, Muhammad Zheeva; Marier, Syauqie Muhammad (Sekolah Tinggi Agama Islam Syekh Abdur Rauf Aceh Singkil, Aceh, Indonesia, 2025)
This research examines the incorporation of Islamic values into Sharia tourism practices in Sapuro, a religious tourism destination in Pekalongan City. The primary issue with this research is the irregularity in applying Islamic principles to manage the pilgrimage area, despite Sapuro being one of the most visited religious destinations in the region. The purpose of this research is to explore the implementation of Islamic values, including cleanliness, comfort of worship, simplicity, halal food, and the sanctity of the place in the infrastructure and services of the destination. The research employed a descriptive qualitative approach, utilizing data collection techniques that included observation, in-depth interviews, and documentation. The results showed that the community and tourism actors have organically internalized Islamic values through social and cultural practices without formal regulatory intervention. The community’s collective consciousness is key to maintaining the destination’s sanctity, comfort, and ethics. This finding is corroborated by Maqashid Sharia theory, which shows that the management of Sapuro has reflected the protection of visitors’ religion, soul, property, and honor. The novelty of this research lies in its community value-based approach to Sharia tourism, which differs from the trend in previous research that emphasizes structural aspects and certification. This research implies the importance of strengthening Islamic value-based participatory governance to build sustainable, spiritually and socially competitive religious destinations. [Penelitian ini mengkaji bagaimana nilai-nilai Islam diinternalisasikan dalam praktik pariwisata syariah di destinasi wisata religi Sapuro, Kota Pekalongan. Permasalahan utama riset ini terletak pada ketidakteraturan dalam penerapan prinsip-prinsip Islam dalam pengelolaan kawasan ziarah, meskipun Sapuro merupakan salah satu destinasi religi yang ramai dikunjungi. Tujuan penelitian ini adalah untuk mengeksplorasi bentuk-bentuk implementasi nilai-nilai Islam, seperti kebersihan, kenyamanan ibadah, kesederhanaan, kehalalan makanan, dan adab kesucian tempat, dalam infrastruktur dan pelayanan destinasi tersebut. Penelitian menggunakan pendekatan kualitatif deskriptif dengan teknik pengumpulan data melalui observasi, wawancara mendalam, dan dokumentasi. Hasil penelitian menunjukkan bahwa nilai-nilai Islam telah diinternalisasi secara organik oleh masyarakat dan pelaku wisata melalui praktik-praktik sosial dan budaya tanpa intervensi regulasi formal. Kesadaran kolektif komunitas menjadi kunci dalam menjaga kesucian, kenyamanan, dan etika destinasi. Temuan ini dikuatkan oleh teori Maqashid Sharia yang menunjukkan bahwa pengelolaan Sapuro telah mencerminkan perlindungan terhadap agama, jiwa, harta, dan kehormatan pengunjung. Kebaruan riset ini terletak pada pendekatan berbasis nilai komunitas dalam pariwisata syariah, yang berbeda dari kecenderungan riset sebelumnya yang menekankan aspek struktural dan sertifikasi. Implikasi dari penelitian ini adalah pentingnya penguatan tata kelola partisipatif berbasis nilai Islam untuk membangun destinasi religi yang berkelanjutan dan berdaya saing secara spiritual serta sosial.]